1997
DOI: 10.1093/nar/25.5.965
|View full text |Cite
|
Sign up to set email alerts
|

Xp54, the Xenopus Homologue of Human RNA Helicase p54, is an Integral Component of Stored mRNP Particles in Oocytes

Abstract: In investigating the composition of stored (maternal) mRNP particles in Xenopus oocytes, attention has focussed primarily on the phosphoproteins pp60/56, which are Y-box proteins involved in a general packaging of mRNA. We now identify a third, abundant, integral component of stored mRNP particles, Xp54, which belongs to the family of DEAD-box RNA helicases. Xp54 was first detected by its ability to photocrosslink ATP. Subsequent sequence analysis identifies Xp54 as a member of a helicase subfamily which inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
126
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(131 citation statements)
references
References 37 publications
4
126
0
1
Order By: Relevance
“…Minshall et al already reported the interaction of Xp54 with eIF4E in Xenopus oocytes (27). In the current study, we also demonstrated the interaction of rck/p54 with eIF4E.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Minshall et al already reported the interaction of Xp54 with eIF4E in Xenopus oocytes (27). In the current study, we also demonstrated the interaction of rck/p54 with eIF4E.…”
Section: Discussionsupporting
confidence: 85%
“…rck/p54 belongs to the RNA helicase SF2/DDX6 subfamily, which is highly conserved from trypanonosomes to humans (15). This subfamily includes Xenopus Xp54 (27), Drosophilla Me31B (28), C. elegans Chh-1 (29) and Saccharomyces cerevisisae Dhh-1 (24). Members of the DEAD-box superfamily are involved in a variety of cellular processes, including splicing, ribosome biosynthesis, RNA transport, translation initiation and RNA decay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZDS2 and ZDS1 are required for G 2 /M progression and SWE1 function and can suppress mutations in numerous genes, mostly cell cycle regulators (Bi and Pringle, 1996;Ma et al, 1996;Schwer and Shuman, 1996;Yu et al, 1996;Mizunuma et al, 1998;Roy and Runge, 2000, and references within). DHH1 is a non-essential DEAD-box helicase that has been implicated in SWE1 function (Strahl-Bolsinger and Tanner, 1993;Warbick and Glover, 1994;Moriya and Isono, 1999), translation (Ladomery et al, 1997), transcription (Hata et al, 1998) and cell cycle arrest under stressful conditions (Maekawa et al, 1994;Bergkessel and Reese, unpublished). RPN11 encodes a regulatory subunit of the 26S proteasome that is required for G 2 /M progression (Glickman et al, 1998;Rinaldi et al, 1998) and for the activation of the transcription factor Gcn4p by UV-induced stress (Stitzel et al, 2001).…”
Section: Isolation Of High Copy Suppressors Of the Taf68-9 Mutantmentioning
confidence: 99%
“…The addition of a sufficient excess of Y-box proteins into in vitro translation systems leads to a translational repression of reporter mRNAs (20 -22). Later studies identified other components of mRNPs, including a DEAD-box ATPase Xp54 and embryonic poly(A)-binding proteins, ePAB and ePABP2 (23)(24)(25)(26)(27). Xp54 and its human homologue RCK repress translation in vitro and/or in oocytes (28,29).…”
mentioning
confidence: 99%